Recent advances in oncolytic virus therapy for hepatocellular carcinoma - Zhu, Licheng; Lei, Yu; Huang, Jia; An, Yahang; Ren, Yanqiao; Chen, Lei; Zhao, Huangxuan; Zheng, Chuansheng (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC), as a highly refractory cancer, which is the fourth leading cause of cancer-related mortality worldwide. Despite the detailed treatment strategy for HCC has been developed, the survival rate is still unsatisfactory. As a new cancer therapeutic agent, oncolytic virus has been widely studied in the treatment of HCC. On the basis of natural oncolytic diseases, researchers have designed a variety of recombinant viruses, which can not only increase the targeting of oncolytic viruses to HCC and their survival in tumors, but also kill tumor cells and inhibit the growth of HCC through a variety of mechanisms, for example, toxic killing effect, activation of immune response, inhibition of tumor angiogenesis, etc. So far, a large number of relevant clinical trials are under way or have been completed, and some encouraging results have been obtained. At the same time, studies have shown that oncolytic virus combined with other HCC therapies may be a feasible method, including local therapy, chemotherapy, molecular targeted therapy and immunotherapy. In addition, different delivery routes for oncolytic viruses have been studied so far. These studies make oncolytic virus a new and attractive drug for the treatment of HCC.